Gaps in the Legal Regulation of Property Rights and other Real Rights in Ukraine: Comparative Characteristics with Similar Institutions in the EU Countries - ILKIV, Oleh; MYKULETS, Vitalii; DUMA, Volodymyr; TKACHUK, Viktor; DEREVIANKO, Nataliia (Revista Jurídica Portucalense, 2023)
The relevance of the study is conditioned by the existence of certain issues related to the registration of property rights and real rights, the grounds for restrictions on such rights, guarantees and ways to protect them, which is extremely important in the state of martial law. The purpose of this study is to investigate the peculiarities of legal regulation of property rights and real rights in Ukraine, as well as to analyse the experience of specific countries of the European Union in this area. The methodological basis of the study consists of a comparative method, methods of system-structural and logical analysis, which allowed establishing the essence of property rights and real rights through the prism of norms regulating relevant relations in Ukraine and the European Union countries; to consider existing problems in the regulatory support of property (private, state, municipal) and real rights; to conduct a comparative analysis of legislative approaches in solving issues of legal regulation of property relations. The main results in the framework of the study should be considered the definition of the features of legal regulation; the emergence, registration, transfer, restriction of property rights and real rights, mechanisms for their protection in Ukraine and in certain European countries; prospects for the development of regulatory support for property rights and other real rights in Ukraine. The relevance of the study results is to provide practical recommendations for improving the legal regulation of relations in the field of property by amending the Civil, Housing, and Land Codes of Ukraine, including individual laws in the field of intellectual property.